Strategi Dakwah di Era Digital: Studi Kasus Podcast Ustadz Adi Hidayat melalui Siaran Youtube - Sofa Rahmadayani Nasution; Elismayanti Rambe (PT. Willy Print Art, 2024)
Dakwah runs continuously from time to time covering various aspects of human life with various ways of conveying information. Wherever, whenever, and in various ways, now someone can study Islam. There are various kinds of social media platforms that can be used as various other social media platforms, Whatsapp, Youtube, Telegram, and so on. Ustadz Adi Hidayat's podcast broadcast on Youtube is a great example of the use of digital platforms to convey religious messages in a way that is engaging and appealing to today's audiences. In this era of advanced technology, podcasts are one of the best ways to preach. The research method applied in this research is by utilizing a library research or literature review. The data used in this descriptive qualitative research comes from searches of several podcast service provider sites as well as several previous studies related to this subject. In today's digital era, podcasts are a good choice for preaching. With this media, dakwah will run more effectively and efficiently, the material presented by the preacher can be listened to again and again without time and place limits.